TIDAK ADA SINONIM DALAM AL-QUR’AN: KAJIAN SEMANTIK TERHADAP KOSAKATA AQL, FIKR, NAZHAR, TADABBUR, DAN ILMU DALAM PERSPEKTIF LA TARADUF - Saputra, Risko Ari; Amin, Sholihuddin; Alamsyah, Muhammad Jiddan Alamsyah; Dasuki, Ahmad (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
This study examines the vocabulary of 'aql, fikr, nazhar, tadabbur, and ʿilm in the Qur'an using a semantic approach and based on the rule of tafsr La Taraduf, namely that there are no absolute synonyms in the Qur'an. Each vocabulary is analyzed in terms of root words, grammatical forms to the context of its use in the verses of the Qur'an and the interpretation of classical scholars. The results show that although the five words are both related to the activity of thinking and knowledge, each has different functions, connotations and scope of meaning. The word aql emphasizes practical reasoning and moral responsibility; fikr points to conscious contemplation, the word nazhar relates to active observation, the word tadabbur leads to deep contemplation of revelation while the word ʿilm covers all forms of knowledge, both rational and revelatory. Thus, this study confirms that the Qur'ān does not convey divine messages with perfectly synonymous words, rather each word has an irreplaceable purpose of meaning.